The Influence of Religiosity, Organizational Culture, Implementation of Internal Controls and Information Asymmetry on Accounting Fraud - Nursifitri, Nadya; Rahayu, Sri; Yudi, Yudi (PT. Riset Press International, 2023)
This study aims to examine the effect of religiosity, organizational culture, internal control implementation, and information asymmetry on accounting fraud in regional apparatus organizations (OPD) Jambi province. The population in this study is the Regional-Dinas Apparatus Organizations, totaling 21 offices in Jambi Province. The sample selected in this study consisted of 3 (three) people, including the Head of OPD, OPD Financial Administrative Officer, and OPD Treasurer, so that the total number of respondents was 63 people. This research data collection technique by distributing questionnaires to research respondents. The data analysis technique used in this study is multiple linear regression analysis. The results of the study found that simultaneously religiosity, organizational culture, internal control implementation, and information asymmetry affects accounting fraud in regional apparatus organizations (OPD) Jambi Province. Partially the variables of religiosity, implementation of internal control, and information asymmetry have an effect on accounting fraud, while organizational culture variables have no effect on accounting fraud.